Steroidogenesis and VEGF production doesn't alter in leydig cells within the homeostatic range of testicular temperature - Atul Kumar Goyal; Jyoti Saini (Wolters Kluwer Medknow Publications, 2018)
Context: Physiologically defined homeostatic temperature range for human testis falls within 32°C-37°C and any deviation outside that range can result in impaired steroidogenesis. However, whether temperature deviation within the homeostatic range can affect the steroidogenesis, is still a question of the investigation. Aim: In the present study, we investigated the production of progesterone, testosterone, and vascular endothelial growth factor (VEGF) within the homeostatic temperature range of testis, i.e., 32°C-37°C. Setting and Design: We used mouse Leydig tumor cells-1 (MLTC-1) cell line as a model in the present study. Materials and Methods: Progesterone and testosterone production by MLTC-1 cells was measured by radioimmunoassay and VEGF production was measured using ELISA. Statistical Analysis Used: Data were analyzed using GraphPad Prism software version 7.04. Student's t-test and ANOVA were used to calculate the P value. P < 0.05 was considered statistically significant. Results and Conclusions: Results of our study indicate that there is no significant difference in production of progesterone, testosterone, and VEGF within the homeostatic range of the testicular temperature. Thus, we concluded that testicular cells are able to regulate the steroidogenesis and VEGF production under the homeostatic range of the testicular temperature.